SOCIALIZATION OF AMELIORANTS AND ORGANIC MATERIALS TO INCREASE SOYBEAN PRODUCTION IN FARMER GROUPS IN KALIMAS VILLAGE, WEST KALIMANTAN - Pustika Adwiyani; Alifiya Herwitarahman; Nurjani; Basuni (Fakultas Pertanian, 2026)
Soybean is an important food commodity in Indonesia; however, domestic production remains insufficient to satisfy national demand. The utilization of acid sulfate tidal lands through the implementation of a saturated soil (waterlogged) system offers a potential strategy to enhance production, although such lands are constrained by high acidity and the presence of toxic elements. The use of ameliorants in combination with organic materials is essential for improving soil physical and chemical properties. Kalimas Village presents considerable potential for soybean cultivation, yet farmers’ knowledge and capacity regarding appropriate cultivation practices and ameliorant application are still limited.This community service program was designed to improve farmers’ knowledge and technical skills by providing both theoretical instruction and practical training on soybean cultivation under a saturated soil system, along with ameliorant application. The program was conducted through several stages, including preparation, outreach, technology dissemination, and subsequent monitoring and evaluation. The findings demonstrated a significant improvement in farmers’ understanding, with 73% of participants recognizing the function of ameliorants and 90% demonstrating comprehension of their application methods. Furthermore, 90% of farmers expressed willingness to adopt the use of ameliorants and organic inputs in soybean cultivation.